Glicerina bruta veiculada à água como suplemento para gestação e início de gestação em ovelhas - Hemilly Cristina Menezes de Sa (2015)
The objective was to first assess the influence of supplementation with crude glycerin (GB) in diets for ewes during pregnancy and early lactation and later its effects on the development of their lambs. We evaluated 24 ewes with Lacaune x East Friesian genotype distributed fully formed randomly into four treatments that differ regarding the supplementation GB (zero, 1.5, 3.0 and 4.5% DM) Therefore, it added water. The dry matter intake (DMI) during pregnancy was reduced by greater supplementation GB, with decreasing linear response and remaining until delivery. During lactation, the variable decreased linearly with supplementing the GB on the eighteenth day of this phase, later showing a quadratic effect until the end of the study period. Water consumption for all treatments was growing during pregnancy with a peak in the second week of lactation. The dry matter digestibility showed a linear reduction in the final third of gestation and early lactation along the fourth to sixth week presented a quadratic behavior. The body score was influenced by GB only in the twenty-fourth day before delivery. The content of -hydroxybutyrate and non-esterified fatty acids were not affected GB supplementation throughout pregnancy. Assessing the birth weight of lambs was found that the GB content explained 5.2% of the observed variation (2), followed by body condition, 2 = 12.3%, sex, 2 = 19.2%, and the weight , 2 = 26.5% to R2 of 63%. Lighter lambs were derived from sheep weighing 40 to 50 kg which had not received GB or higher levels and had a score between 4 and 5, in contrast to the heavier lambs with a birth weight greater than 5.5, came from heavy sheep between 80 to 90 kg who received levels 2-4% of GB and had a low score. The chemical composition and physical chemistry from sheep's milk was not affected by supplementation GB in the water. Supplementation with GB conveyed water-pregnant ewes and in early lactation reduced the DMI, did not negatively affect the production and composition of milk and blood parameters.